2018
DOI: 10.3174/ajnr.a5908
|View full text |Cite
|
Sign up to set email alerts
|

Bias in Neuroradiology Peer Review: Impact of a “Ding” on “Dinging” Others

Abstract: BACKGROUND AND PURPOSE: The validity of radiology peer review requires an unbiased assessment of studies in an environment that values the process. We assessed radiologists' behavior reviewing colleagues' reports. We hypothesized that when a radiologist receives a discrepant peer review, he is more likely to submit a discrepant review about another radiologist. MATERIALS AND METHODS: We analyzed the anonymous peer review submissions of 13 neuroradiologists in semimonthly blocks of time from 2016 to 2018. We de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…7,10,11 One study found that radiologists were more likely to submit a discrepant peer review report within a semi-monthly block of time after receiving one, suggesting another source of bias. 12 An important drawback to peer review of randomly selected cases is that they rarely reveal clinically significant discrepancies, and therefore have low yield for learning. In a study that reviewed over 42 000 reports over 42 months, the potentially meaningful discrepancy rate was only 0.5%, and usage of the peer review system declined by 56% between the first and last quarters of the study period.…”
Section: Drawbacks Of Traditional Peer Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…7,10,11 One study found that radiologists were more likely to submit a discrepant peer review report within a semi-monthly block of time after receiving one, suggesting another source of bias. 12 An important drawback to peer review of randomly selected cases is that they rarely reveal clinically significant discrepancies, and therefore have low yield for learning. In a study that reviewed over 42 000 reports over 42 months, the potentially meaningful discrepancy rate was only 0.5%, and usage of the peer review system declined by 56% between the first and last quarters of the study period.…”
Section: Drawbacks Of Traditional Peer Reviewmentioning
confidence: 99%
“…7,10,11 One study found that radiologists were more likely to submit a discrepant peer review report within a semi-monthly block of time after receiving one, suggesting another source of bias. 12…”
Section: Drawbacks Of Traditional Peer Reviewmentioning
confidence: 99%